2020
DOI: 10.1016/j.gaitpost.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Validity of various portable devices to measure sit-to-stand velocity and power in older adults

Abstract: The authors would like to thank Ray Schofield and Christopher Jones for their help in recruitment and data collection. We would also like to thank all the volunteers whom volunteered to take part in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…The HIIT protocol used in this study recommended inclusion of supervised sessions (i.e., 6 WMT is the most commonly applied measure of endurance walking capacity and is valid for estimating VO 2max in the elderly. Improvements in the 6WMT are valuable goals for the elderly in whom functional capacity is severely compromised [51]. Our meta-analysis data also revealed that HIIT has the potential to increase 6WMT by 65.82 m, which is consistent with previous data that demonstrated that HIIT can up-regulate the 6WMT by 68 m in the elderly [28].…”
Section: Blood Pressure and Ef%supporting
confidence: 90%
“…The HIIT protocol used in this study recommended inclusion of supervised sessions (i.e., 6 WMT is the most commonly applied measure of endurance walking capacity and is valid for estimating VO 2max in the elderly. Improvements in the 6WMT are valuable goals for the elderly in whom functional capacity is severely compromised [51]. Our meta-analysis data also revealed that HIIT has the potential to increase 6WMT by 65.82 m, which is consistent with previous data that demonstrated that HIIT can up-regulate the 6WMT by 68 m in the elderly [28].…”
Section: Blood Pressure and Ef%supporting
confidence: 90%
“…Due to their small size and portability, triaxial accelerometers were the first devices to be used to monitor physical activity and/or everyday movements in different settings [ 8 , 24 , 25 , 26 ]. More recently, some studies have investigated the relevance of using smartphones with incorporated accelerometers in clinical settings [ 27 ] and more particularly for the assessment of the STS [ 2 , 28 , 29 , 30 , 31 ]. Many studies have therefore attempted to evaluate STS movements with either a single accelerometer or multiple accelerometers, both embedded and not embedded in smartphones, placed over different regions of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Gripwise—a small, light, and portable wireless device—has been developed to accurately measure handgrip strength via BLE communication, with good sensitivity, resolution and precision (for technical details, please see reference [ 31 ]), and has already been validated against the Jamar [ 32 ] (commonly considered the gold standard device for handgrip strength evaluation). The five-repetition sit-to-stand test evaluation method follows the commonly used protocol [ 33 ] in which participants sit on the edge of an armless chair with arms crossed against their chest and with hips, knees, and ankle joints at approximately 90 degrees. Participants are instructed to stand upright as quickly as possible (with a full extension of the hips and knees) and then to sit back down to the initial position.…”
Section: System Workflowmentioning
confidence: 99%